Analisis Sensori Minuman Instan Ekstrak Jahe Gajah, Jahe Emprit Dan Jahe Merah - Razi, Ramadhani Ar; Ariyetti, Ariyetti; Kasim, Anwar (CV.ITTC INDONESIA, 2024)
Ginger is one of the herbal plants that has many benefits, especially for health. Ginger functional drink was developed in powder form so that it is more practical for consumption. The purpose of this study was to determine panelists preference for ginger extract instant drinks from 3 different types of ginger, namely: elephant ginger, emprit ginger and red ginger. Sensory assessment was done descriptively and hedonic which includes color, taste and aroma of the ginger instant drink produced. The sensory results of ginger extract instant drink were color 3.55 (like) - 3.8 (like); taste 3.05 (normal) - 3.45 (normal) and aroma 3.5 (normal) - 3.85 (like). The results showed that panelists preferred the red ginger extract instant drink.